Clinical and histopathological characterization of paradoxical head and neck erythema in patients with atopic dermatitis treated with dupilumab: a case series. (1st October 2020) - de Wijs, L.E.M.; Nguyen, N.T.; Kunkeler, A.C.M.; Nijsten, T.; Damman, J.; Hijnen, D.J.
Summary: Dupilumab is the first biologic registered for the treatment of atopic dermatitis (AD). We report on seven patients with AD presenting with a paradoxical head and neck erythema that appeared 10–39 weeks after the start of dupilumab treatment. The patients presented with a relatively sharply demarcated, patchy erythema in the head and neck area that showed no or less scaling compared with their usual eczema. Only one patient experienced symptoms of itch and burning, although this was notably different from his pre‐existent facial AD. Except for a notable 'red face', eczema on other body parts had greatly improved in six of the seven patients, with a mean numerical rating scale for treatment satisfaction of 9 out of 10 at the time of biopsy. Treatment of the erythema with topical and systemic drugs was unsuccessful. Despite the presence of this erythema, none of our patients discontinued dupilumab treatment. Lesional skin biopsies showed an increased number of ectatic capillaries, and a perivascular lymphohistiocytic infiltration in all patients. In addition, epidermal hyperplasia with elongation of the rete ridges was observed in four patients, resembling a psoriasiform dermatitis. Additional immunohistochemical stainings revealed increased numbers of plasma cells, histiocytes and T lymphocytes. Interestingly, spongiosis was largely absent in all biopsies. We report on patients with AD treated with dupilumab developing a paradoxical erythema in a head and neck distribution. Both clinically and histopathologically we found a heterogeneous response, which was most suggestive of a drug‐induced skin reaction.